2006
DOI: 10.1248/yakushi.126.1191
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Interactions between Prescription Drugs and OTC Drugs (2nd Report)-Interaction between Levodopa Preparation and OTC Kampo Medicines for Upset Stomach-

Abstract: Our series of studies aimed to examine the possibility of interactions between prescription drugs and over-the-counter (OTC) drugs by monitoring plasma drug concentrations in rats. When a levodopa preparation indicated for patients with Parkinson's disease was administered in combination with Takeda Kampo Ichoyaku K-matsu (A), Taisho Kampo Ichoyaku (B), or Kanebo Kampo Ichoyaku H(C), which are OTC kampo medicines for upset stomach, the plasma levodopa concentration-time curves were shifted downward and the AUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Herb-drug interactions may affect all these stages, thus possibly resulting in a decreased therapeutic effect of levodopa. Preliminary in vivo results demonstrated that levodopa, when in combination with over the counter (OTC) drugs used for stomach burning (Table 1), resulted in a significantly lower area under the curve (AUC) for levodopa (Sunagane et al, 2006). However, these results were not supported by a concise explanation or hypothetical mechanisms.…”
Section: Interactions With Levodopamentioning
confidence: 99%
“…Herb-drug interactions may affect all these stages, thus possibly resulting in a decreased therapeutic effect of levodopa. Preliminary in vivo results demonstrated that levodopa, when in combination with over the counter (OTC) drugs used for stomach burning (Table 1), resulted in a significantly lower area under the curve (AUC) for levodopa (Sunagane et al, 2006). However, these results were not supported by a concise explanation or hypothetical mechanisms.…”
Section: Interactions With Levodopamentioning
confidence: 99%
“…For example, branched-chain amino acids may be administered to stimulate appetite; however, this resembles a high-protein diet, which may induce levodopa wearing off. Herbal remedies for dyspepsia, particularly those with metallic additives, have been shown to inhibit levodopa absorption [123] and may also worsen motor complications; thus, these remedies should be avoided in patients with PD.…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%
“…HM use has increased over the last two decades in various places, both developed and developing countries [4][5][6][7]. Along with the rise in their use comes the risk of interaction with conventional medicines when prescribed [8][9][10]. The potential for interaction between herbs and prescription drugs is of concern because the pharmacokinetics of one or more medications taken simultaneously can be altered and can lead to clinically significant toxicities [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%